2013
DOI: 10.4172/2324-9323.1000124
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Defaults in the Prevention of Pediatric Obesity: From Platform to Practice

Abstract: The term “optimal defaults” refers to imparting pre-selected choices which are designed to produce a desired behavior change. The concept is attractive to policymakers because it steers people toward desirable behaviors while preserving free choice through the ability to opt out. It has been found to be a powerful behavioral determinant in areas such as pension plan enrollment, organ donation, and green energy utilization. We discuss how optimal defaults can be applied to pediatric obesity prevention in severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 100 publications
3
10
0
Order By: Relevance
“…Currently there is focus on implementing population-based approaches to reduce the availability and acceptability of SSBs. These approaches tend to be environment-centred and policy-driven, rather than individual-centred: they aim to change the environment to one of health promoting choices or ‘optimal defaults’ [ 7 ]. These approaches require lower levels of personal responsibility or ‘agency’ from individuals to change their behaviour and aim to create environments that readily enable healthier choices [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently there is focus on implementing population-based approaches to reduce the availability and acceptability of SSBs. These approaches tend to be environment-centred and policy-driven, rather than individual-centred: they aim to change the environment to one of health promoting choices or ‘optimal defaults’ [ 7 ]. These approaches require lower levels of personal responsibility or ‘agency’ from individuals to change their behaviour and aim to create environments that readily enable healthier choices [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Postprandial blood glucose response, which is a risk factor for micro- and macro-vascular complications, has been shown to be influenced profoundly by the specific composition of the diet [ 31 ]. The measure of how soon glucose reaches the blood stream is often termed the glycaemic index (GI) of food while the glycaemic load (GL) shows the overall glycaemic effect of a specific amount of food item [ 1 ]. It is possible that DSFs are formulated with carbohydrates which have lower GI compared with standard formulas.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of diabetes and the cost to the National Health Service (NHS) have been on the increase in the UK [ 1 , 2 ]. Various factors including the failure to maintain a healthy lifestyle such as regular physical activity and healthy dietary regimes, and genetic susceptibility have been ascribed as possible reasons for the high incidence of the condition [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] Improving nutrition policies and practices, such as limiting low-nutrient, high-energy density foods, and sweetened beverages, offering more fresh fruits and vegetables, improving feeding practices, and providing quality nutrition education have been shown to be effective and sustainable, yet many child care providers have not fully implemented these optimal policies and practices. [11][12][13][14] Two recent reviews of obesity prevention interventions in early childhood education centers found positive changes in physical activity, diet, and weight status, especially multicomponent interventions with parent engagement components. [15][16][17] However, to the authors' knowledge, there are no published studies in family child care homes (FCCs).…”
mentioning
confidence: 99%